Asphalt concrete pavement strengthening and modelling of its effect on road evenness/Asfaltbetonio dangų stiprinimas ir jo įtakos kelio lygumui modeliavimas - Puodžiukas, Virgaudas; Kamaitis, Zenonas (Journal of Civil Engineering and Management, 1999)
Lithuania has a sufficiently well-developed road network, the quality of which still falls very much behind the standards used in the EU. The process of pavement distress is gradually accelerated by the following factors: a considerable increase in the amount of heavy vehicles, acceptance of 11.5 t permissible axle load within the EU member-states (10.0 t in the former Soviet Union), overloading of heavy vehicles. Under the influence of the mentioned factors the need for pavement strengthening is very urgent. When preparing this article, several methods for the evaluation and strengthening of asphalt concrete pavement condition were studied: “Deflection method” by Asphalt Institute of USA [1], AASHTO Guide [2], “The method for asphalt concrete pavement condition evaluation” by Vilnius Technical University, OECD recommendations on pavement strengthening [9], EU recommendations COST 324 [3] and COST 325 [4], HDM-III [5] and HDM-4 [6] recommended by the World Bank and a number of scientific articles. On this basis, methodology for Lithuanian conditions was worked out taking into consideration the current technologies for road construction and maintenance. This article describes the evaluation of pavement strength and the need for pavement strengthening, gives the analysis of the effect of pavement strengthening on road evenness. It is suggested that the pavement strength should be evaluated by estimating the Structural Number SN of the existing pavement according to the results of pavement deflections measured by FWD (the authors used “Dynatest 8000 FWD”). The following relationship is suggested for determining thickness of the overlay (see Eq (5)).Dol = 2,54SNol /αol = 2,54(SNf —SNe )/αol , where D ol is thickness of the overlay, cm; SNol is structural number of the overlay; αol is structural coefficient of the overlay; SNf is structural number of prospective pavement; SNe is structural number of the existing pavement. The article studies the effect of overlay and pavement regeneration on road evenness. The effect of pavement strengthening on road evenness is to be estimated by the following relationship (see Eq (6)):IRI′ = a0 + a1(IRI—a0)max(a2—HNEW), where IRI is the measured pavement evenness before the repairs, m/km; HNEW is thickness of the overlay, mm. Experimental investigations of 64 test road sections were carried out and the value of coefficients a0, a1 and a2 was determined under the Lithuanian conditions. New coefficients provide the opportunity for a more accurate evaluation of the effect of pavement strengthening on road vehicles and for a more realistic estimation of savings road user's costs due to improved pavement condition. Only on the motorway Vilnius-Kaunas-Klaipėda, when estimating VOC savings according to the suggested method, the difference of 37 m Lt was obtained, if compared to the theoretical methods.Article in Lithuanian.First Published Online: 26 Jul 2012